Pengaruh Metode Guided Note-Taking Berbantuan Powerpoint Interaktif terhadap Hasil Belajar Peserta Didik Kelas V Sekolah Dasar - Gilang Rifqi Ardhiansyah; Surya Hutama, Fajar; Ayu Puspitaningrum, Dyah; Zahroul Fitriyah, Chumi; Aguk Wardoyo, Arik (Jurnal Gentala Pendidikan Dasar, 2023)
The background of this research is that there is a lack of optimality in the learning process at SDN 1 Mangkujayan Ponorogo, so that the learning outcomes obtained are not maximal. The causal factor is the use of conventional learning methods or lectures in daily learning activities. This research was conducted to determine the effect of using the method guided note-taking help powerpoint interactive to student learning outcomes. The type of research used is an experimental design non equivalent control group and quasi-experimental patterns. Method guided note-taking is a learning technique that aims to improve students listening skills, concentration, activeness, and understanding when studying large amounts of material through handout provided by the teacher. The results of this study show from testing t-test results obtained tcount= 6.127, greater than ttable at a significance level of 5% with db 56 is 1.671. This shows that tcount (6,127) > ttable (1.671) which means H0 rejected and Ha accepted. The conclusion from the research that has been carried out is that there is a significant influence from the use of the method guided note-taking media-assisted powerpoint interactive learning outcomes for students in class V theme 8 sub-theme 1 SDN 1 Mangkujayan Ponorogo.